Toxic Plant Metabolites, Cyanogenic Glycosides, Poisoning Mechanisms, Health Risks, and Analytical Method Development for Detecting Toxicants in Food - Bhandare, Saurabh Dilip; Malode, Sarika Shivaji (Food and Drug Safety, 2026)
This study presents a novel robust titrimetric analysis method for detection and quantification of cyanide in food samples artificially spiked with cyanogenic compounds derived from bamboo and cassava species. The titration approach demonstrated a strong linear correlation between cyanide concentration and the volume of titrant required for complete neutralisation. Cyanogenic glycosides are naturally occurring plant toxins that can release hydrogen cyanide (HCN) upon enzymatic hydrolysis, posing a significant risk to human health. These compounds are found in various plants, including bitter almonds, cassava, and wild cherries, and play a defensive role against herbivorous. However, their presence in food sources raises concerns about accidental poisoning, neurotoxic syndromes like tropical ataxic neuropathy and Konzo disease, and potential long-term health effects. Food safety concerns, detoxification methods, and strategies to minimise cyanogenic risks through proper food processing and dietary awareness. Understanding these toxic secondary metabolites is crucial for ensuring food safety and preventing health hazards associated with plant-based diets and traditional herbal medicine practices. Results showed that increasing cyanide levels directly corresponded to higher titrant volumes, with 2 ppm cyanide requiring 22 mL of titrant and 25 ppm requiring 550 mL, confirming the method’s reliability. Comparison with standard cyanide detection protocols validated the accuracy and consistency of the titrimetric technique. Reproducibility of results across different concentrations and sample types highlights the robustness and precision of this method, making it suitable for cyanide monitoring in various food matrices. This approach offers a practical, robust novel analytical-technique for routine food safety analysis, particularly in toxicological analysis.